Consumer Energy Conservation Behavior After Fukushima Evidence from Field Experiments - Matsukawa, Isamu; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
This book presents an in-depth empirical analysis of consumer response to alternative policies for energy conservation. Its main focus is on innovative policy instruments that have attracted increasing attention from academics and energy conservation practitioners alike: critical peak pricing, conservation requests, in-home displays, and home energy reports. The book investigates the effects of these policy instruments on residential demand for electricity. The data is drawn from a series of randomized field experiments for the years 2012-2013 in Japan, where serious concerns about power shortages have emerged in the wake of the nuclear disaster in Fukushima. By applying econometric techniques to the quantitative analysis of residential power consumption, the book demonstrates how consumers respond to innovative instruments for energy conservation. It also offers new perspectives on how these instruments can be used more effectively and explores the potential for their practical implementation. This highly informative book is essential reading for energy specialists in both academic and professional contexts.
Keywords: Natural Resource and Energy Economics; Energy Policy, Economics and Management; Behavioral/Experimental Economics